Distinct pools of dissolved iron‐binding ligands in the surface and benthic boundary layer of the California Current - Randelle M. Bundy; Dondra V. Biller; Kristen N. Buck; Kenneth W. Bruland; Katherine A. Barbeau (Limnology and Oceanography, 2014)
Organic dissolved iron (dFe)—binding ligands were measured by competitive ligand exchange—adsorptive cathodic stripping voltammetry (CLE‐ACSV) at multiple analytical windows (side reaction coefficient of salicylaldoxime, α Fe(SA) 2 = 30, 60 and 100) in surface and benthic boundary layer (BBL) samples along the central California coast during spring and summer. The weakest ligands were detected in the BBL at the lowest analytical window with average log K cond FeL,Fe' = 10.2 ± 0.4 in the summer and 10.8 ± 0.2 in the spring. Between 3% and 18% of the dFe complexation in the BBL was accounted for by HS, which were measured separately in samples by ACSV and may indicate a source of dFe‐binding ligands from San Francisco Bay. The strongest ligands were found in nearshore spring surface waters at the highest analytical window with average log K cond FeL,Fe' = 11.9 ± 0.3, and the concentrations of these ligands declined rapidly offshore. The ligand pools in the surface and BBL waters were distinct from each other based on principal components analysis, with variances in the BBL ligand pool explained by sample location, and variance in surface waters explained by water mass. The use of multiple analytical window analysis elucidated several distinct iron‐binding ligand pools, each with unique distributions in the central California Current system.

Life cycle contributions of copper from vessel painting and maintenance activities - Patrick J. Earley; Brandon L. Swope; Katherine Barbeau; Randelle Bundy; Janessa A. McDonald; Ignacio Rivera-Duarte (Biofouling, 2014)